Self-sensing performance of strain hardening geopolymer composite - Nur Fazirah Mohamed Faizal (Nanyang Technological University, 2021)
Self-monitoring of strain-hardening geopolymer composites (SHGPC) has been a growing research topic due to the possibility of the composite’s capability in structural health monitoring. SHGPC is known for its exceptional mechanical properties and self-sensing ability through alterations in its electrical resistivity. Studies done in the past have proven that modification of the interface between the fibre and matrix could substantially enhance the matrix’s mechanical and sensing properties. In this study, Polyethylene (PE) fibres will be coated with Carbon Nanofibre (CNF) to determine if these conductive CNFs could strengthen the sensitivity of self-sensing ability and improve its mechanical strength. The resistivity of CNF-coated SHGPC is measured through a two-probe method under uniaxial tensile loading. The influence of CNF-coated fibres added to composites will be analysed to establish the sensitivity of the material to strain changes.